Islamic Law and the Blasphemy Debate in Contemporary Indonesia - Mufidah, Mufidah; Hartiwiningsih, Hartiwiningsih; Isharyanto, Isharyanto; Wardi, Musa (AHKAM : Jurnal Ilmu Syariah, 2024)
Blasphemy is a sensitive and complex issue in Indonesia, the largest Muslim-majority country in the world. This article examines the regulation of blasphemy, which often clashes with Indonesia's social, cultural, and political dynamics. It evaluates the reconstruction of blasphemy laws through the lens of maqāṣid al-‘uqūbāt in Islamic law. The study concludes that reconstructing the blasphemy law is necessary as part of legal reform that aligns with Indonesia's constitutional principles of the rule of law and democracy. This reconstruction should integrate Islamic legal principles based on maqāṣid al-‘uqūbāt in several key areas, including defining the legal subjects of blasphemy, providing clarification as part of the resolution process by considering shubhāt and al-dan ta'wīl, and developing mechanisms for resolving blasphemy cases. The urgency for reform arises from several critical factors: the ambiguous formulation of blasphemy norms, which significantly impacts court decisions; the absence of consistent justice-based law enforcement mechanisms; disparate treatment toward certain groups; and the tendency to generalize blasphemy cases as criminal acts due to a lack of alternative measures. These issues reflect legal uncertainty and the potential misuse of blasphemy laws for political purposes.AbstrakPenistaan agama merupakan isu yang sensitif dan kompleks di Indonesia, negara berpenduduk mayoritas Muslim terbesar di dunia. Artikel ini mengkaji pengaturan penodaan agama yang sering kali berbenturan dengan dinamika sosial, budaya, dan politik di Indonesia. Artikel ini mengevaluasi rekonstruksi hukum penodaan agama melalui lensa maqāṣid al-'uqūbāt dalam hukum Islam. Penelitian ini menyimpulkan bahwa rekonstruksi undang-undang penodaan agama diperlukan sebagai bagian dari reformasi hukum yang selaras dengan prinsip-prinsip konstitusional Indonesia tentang negara hukum dan demokrasi. Rekonstruksi ini harus mengintegrasikan prinsip-prinsip hukum Islam berdasarkan maqāṣid al-'uqūbāt di beberapa bidang utama, termasuk mendefinisikan subjek hukum penodaan agama, memberikan klarifikasi sebagai bagian dari proses penyelesaian dengan mempertimbangkan syubhat dan al-ta'wīl, dan mengembangkan mekanisme penyelesaian kasus penodaan agama. Urgensi reformasi muncul dari beberapa faktor kritis: rumusan norma penodaan agama yang ambigu, yang secara signifikan berdampak pada putusan pengadilan; ketiadaan mekanisme penegakan hukum yang berbasis keadilan yang konsisten; perlakuan yang tidak adil terhadap kelompok-kelompok tertentu; dan kecenderungan untuk menggeneralisasi kasus-kasus penodaan agama sebagai tindakan kriminal karena kurangnya upaya-upaya alternatif. Isu-isu ini mencerminkan ketidakpastian hukum dan potensi penyalahgunaan undang-undang penodaan agama untuk tujuan politik.